PELAKSANAAN PERKAWINAN PADA MALAM SONGO RAMADHAN SEBAGAI LOCAL WISDOM DI MASYARAKAT PARENGAN KABUPATEN TUBAN - Nurul Novitasari (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2023)
This study is about wedding culture on Songo Ramadlan night in Parengan Tuban, East Java. In this research location, there is a wedding tradition called malem songo that has been passed down from generation to generation and it is not known for certain when this tradition was first implemented.. Seeing this, the researcher carried out research with the aim of (1) knowing the factors that cause marriages to occur on the night of the 29th of the month of Ramadan in the community of Parengan District, Tuban Regency (2) to find out the perspective of customary law and Islamic law on the occurrence of marriages on the night of the 29th of Ramadhan in the people of Parengan District, Tuban Regency. This research uses a type of empirical legal research where all information is obtained from documentation and interviews, using a qualitative approach. Meanwhile, the data collected is primary data, namely interviews with Parengan District KUA officials, figures and several community members who held weddings at Night Songo and secondary data from books that have relevance in research, which is then edited, checked and compiled carefully and arranged in such a way analyzed. The results of this research show that getting married at night songo has become a tradition and is deeply rooted in the people of Parengan District, which is considered to bring blessings in Javanese culture and is seen as a form of local wisdom. Therefore, the implementation of this marriage is to avoid complications, because the Songo Ramadhan night is not regulated by religious principles or Javanese law.